2011
DOI: 10.1089/omi.2010.0128
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Sex Hormone-Related Pathways in Benign and Malignant Human Prostate Tissues: Data of a Preliminary Study

Abstract: Prostate cancer (PCa) is a major health issue in Westernized countries, representing a common cause of morbidity and mortality in the elderly male population. Endogenous sex steroids, along with environmental factors (notably diet) and host immune and inflammatory responses, are likely to cooperate in the pathogenesis of the disease. Based on the assumption that a complex endocrine-inflammatory-immune interaction is primarily implicated in human PCa, we have investigated the interplay between sex steroids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It has been reported that the leucine allele reduces almost 30% of androstanediol glucuronide, a serum marker of 5α-reductase activity, among Asian men. Among Caucasian men, a 10% insignificantly lower androstanediol glucuronide level has been observed in individuals with the L/L genotype (12).…”
Section: Srd5a2mentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that the leucine allele reduces almost 30% of androstanediol glucuronide, a serum marker of 5α-reductase activity, among Asian men. Among Caucasian men, a 10% insignificantly lower androstanediol glucuronide level has been observed in individuals with the L/L genotype (12).…”
Section: Srd5a2mentioning
confidence: 95%
“…They found that short AR and C/T genotypes of aromatase have a 3-fold increase in risk for PC in a Japanese population (14). Using a "super control" group composed of male Sicilian centenarians, Balistreri et al observed a significant difference in genotype distribution of Arg264Cys between PC patients and controls (12). However, other large studies have failed to confirm the association of rs700519 with PC in different populations (18).…”
Section: Cyp19mentioning
confidence: 99%
“…Moreover, in the genotype TT of rs700518 population, E2 was significantly higher in BPH (46.73 ± 16.38 pg/mL), MetS (46.80 ± 21.32 pg/mL), and MetS‐BPH (47.12 ± 22.13 pg/mL) groups than the overall average of 38.62 ± 17.43 pg/mL (see Tables and ). Compared with previous research (Chen et al ., ; McTernan et al ., ; Simpson et al ., ; Burnett‐Bowie et al ., ; Santen et al ., ; Balistreri et al ., ; Berges et al ., ; Ho & Habib, ; Cornu et al ., ), our results illustrate the CYP19A1 gene single nucleotide polymorphisms in the Chinese population distribution and reveals that the genotype TT of rs700518 may be a common susceptible factor of BPH, MetS, and MetS‐BPH. Also, it is done by increasing the metabolism of estrogen.…”
Section: Discussionmentioning
confidence: 98%
“…, which is through CYP19A1 SNPs, especially through increasing the genotype TT of the rs700518 gene expression, which causes the metabolism level of estrogen to increase, leading to a reduction in the T/E ratio; this triggers IR, raises blood glucose levels, and promotes hyperplasia of prostate gland acinar cells and stromal cells in the prostate tissue, leading to the occurrence of clinical BPH and MetS. In contrast, BPH can lead to a systemic metabolic disorder, which can lead to IR, resulting in MetS (Crawford et al ., ; Balistreri et al ., ; Ersekerci et al ., ; Cornu et al ., ). Moreover, through IR, MetS and BPH interact and progress clinically.…”
Section: Discussionmentioning
confidence: 99%
“…There are several polymorphisms in the ER-α gene and some of them are associated with the risk of prostate cancer (Fukatsu et al 2004;Hernández et al 2006;Balistreri et al 2011;Sissung et al 2011;Safarinejad et al 2012). In the present study, we decided to continue with our previous research (Jurečeková et al 2013) and we analyzed other two polymorphisms (rs2077647 and rs3798577) in ER-α gene, which connection with prostate cancer is not explicitly confirmed or denied.…”
Section: Introductionmentioning
confidence: 99%